Basic English Training in an Effort to Instill Student Interest in Entering Health Schools - Purwani, Retno; Syahrudin , M. Eki (Devotion : Journal of Research and Community Service, 2021)
English teaching quality is not distributed evenly throughout the region in Indonesia. The tendency is for students that live in big cities, they get more qualified English teaching than remote areas. In other side, Student who come from village are far from big city. Students expected that study at Health Education must have good English skill. It effects to Senior High School student unwilling to study at Health School because they have less skill in Basic English. Moreover, they didn’t have enough money to getting facilities to study more outside of school, although they need it. Finally their human resource capabilities are down. So, the Basic English skill need to improve to improve the human resource capability in the field of Englis.in this dedication, Basic English trainee will be given to students of MA Al-Istiqomah that need increasing of capacity. There are 8 meets by enjoyable studying, beside pretest and posttest. The result was English skill increase. But its need seriously study from the students so the English skill will be increase significantly. So English Trainee Program for students can help human resouces in English